Stress levels in families where there is an alcoholic male adult : a twelve month study : a thesis presented in fulfillment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University - Bellamy, Joan Elizabeth Guyer (Massey University, 1989)
There has been a growing interest in the effects of stress in families where there is an alcohol problem. The present study tested the hypotheses that: A. alcoholic families evidence higher stress levels than matched control group families and B. that alcoholic families receiving stress management sessions evidence lower stress levels at one year follow-up than matched control group alcoholic families that did not receive stress management sessions. In the first part of the study, forty families that had an alcoholic adult male were identified upon request for alcohol treatment. Matched Medical and Community control groups were available and data was obtained from all groups. In the second part of the study, one half of the forty identified alcoholic families received stress management sessions, the remaining twenty received no stress management follow-up. In support of Study I hypothesis and data obtained from family stress level measurements, there was indicated a significant difference in stress levels on several variables between alcoholic and non-alcoholic families. In support of the Study II hypothesis those twenty alcoholic families receiving stress management showed a significant lower stress level at one year follow-up than the twenty alcoholic families that did not receive stress management. The study also indicates trends in families of alcoholic males that show these families have higher stress levels and make more visits to their medical doctors than do control group families.
Keywords: Stress (Psychology); Effect of alcoholism on family; Problem families